Surveillance of Bacterial Pathogens in Children with Acute Diarrhea in Chiang Rai Province, Thailand - Yowang, Amara; Uttiyoung, Thanida; Somngen, Anchitha; Chaiwongsan, Phanuphong (Journal of Health Science of Thailand, 2017)
Acute diarrhea diseases are an important health problem in Thailand with high prevalence in children less than 5 years old. The incidence of this group of diseases has been the highest among other notifiable diseases under the current surveillance program. Therefore, the Regional Medical Science Center No.13 had developed a project to identify the bacteria that caused acute diarrhea. In this study, bacterial pathogen identification was performed among all 611 stool samples collected from acute diarrhea patients aged between 3 months and 5 years who received treatment in hospitals in Chiang Rai province between May 2008 and April 2010. It was found that Salmonella was detected in 14.6% of the samples, Aeromonas in 8.6%, Campylobacter in 8.3%, Plesiomonas in 4.8% and Shigella in 1.6%. This implied that food sanitation in the study areas might need to be improved. However, acute diarrhea in children is also caused by other types of pathogens such as virus or parasites. Hence, rapid laboratory diagnosis to differentiate the type of pathogens is essential to assist clinical responses and support disease monitoring, forecasting surveillance and effective control.